STUDI PERILAKU PENGGUNAAN EARPLUG PADA PEKERJA BAGIAN PRODUKSI DI PT X TAHUN 2019 - Herbert Wau; M. Rizki Fadirah Harahap; Ermi Girsang (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2020)
PT X is a national private company engaged in agribusiness in the form of rubber processing with a noise level of 100.1 dB. PT.X found that there were 11 hearing impaired workers. Workers who are in a work environment with noise at> 85 dB do not use APT (Earplug) and are at risk for experiencing occupational diseases, namely deafness. The purpose of this study was to determine the Study of Behavior in the Use of APT (Earplug) in production section workers at PT X. This research is descriptive analytic, with a cross sectional research design. The population in this study were all workers who worked at PT X. The sample in this study was taken with a total sampling technique of 39 employees. Data collection techniques by observation and questionnaire. Analysis of the data used in this study was the Chi-Square test (95% CI). Based on the results of the Univariate test, it is known that the majority of respondents are 30-39 years old (16 people), the majority of high school / vocational school educated (26 people), the majority of respondent working duration> 2 years (36 people). Chi-Square Test results obtained that there is a relationship between attitude (p = 0.037) and action (p = 0.000) with the use of APT at PT X, while knowledge is not related to the use of APT at PT X, where, Knowledge with a value of p = 0.238, while the attitude with the use of APT value p = 0.037 and the action with a value of p = 0.000 so that there is a relationship between Attitudes and Actions towards the use of APT in Production Section Workers at PT X, Simalungun, 2019. The conclusion is there is no relationship between knowledge and the use of APT and there is relationship between attitude and action with the use of APT